Makna Tuturan dalam Podcast Agak Laen Bersama Halda Rianta: Analisis Semiotika Ferdinand de Saussure - Anggi Nur Rahma; Annisa Nabila Siregar; Arika Simehate; Risa Novianti; Bungsu Keumala Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Early marriage remains a common social reality in Indonesia and is often associated with a higher risk of divorce due to a lack of emotional, psychological, economic, and knowledge-based preparedness in building a family. This phenomenon has also developed on new media platforms such as podcasts, one of which is the Agak Laen Podcast featuring Halda Rianta, which explicitly states that early marriage accelerates divorce. This study aims to analyze the meaning of utterances in the podcast using Ferdinand de Saussure's semiotic approach, which views a sign as a unity between the signifier and the signified, whose relationship is arbitrary yet determined by social convention. A qualitative descriptive method was employed, with data collected through documentation and note-taking of Halda Rianta's verbal utterances, analyzed by identifying the relationship between signifier and signified. The findings reveal three main constructions of meaning: first, the utterance